2020
DOI: 10.1186/s12883-020-01930-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy of COVID-19 positive acute ischemic stroke patient: a case report and call for preparedness

Abstract: Background The novel coronavirus (COVID-19) global pandemic is associated with an increased incidence of acute ischemic stroke (AIS) secondary to large vessel occlusion (LVO). The treatment of these patients poses unique and significant challenges to health care providers requiring changes in existing protocols. Case presentation A 54-year-old COVID-19 positive patient developed sudden onset left hemiparesis secondary to an acute rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
9
1
1
Order By: Relevance
“… Kwan J, UK [ 49 ] Good Good Fair Fair Good Good Good Good Good 7. Mansour OY, Egypt [ 50 ] Good Fair Fair Fair Good Fair Good Good Good 8. McConachie D, UK [ 51 ] Good Good Good Good Good Good Good Good Good 9.…”
Section: Main Text (Review Of the Literature Results Discussion)mentioning
confidence: 99%
See 3 more Smart Citations
“… Kwan J, UK [ 49 ] Good Good Fair Fair Good Good Good Good Good 7. Mansour OY, Egypt [ 50 ] Good Fair Fair Fair Good Fair Good Good Good 8. McConachie D, UK [ 51 ] Good Good Good Good Good Good Good Good Good 9.…”
Section: Main Text (Review Of the Literature Results Discussion)mentioning
confidence: 99%
“… 7. Mansour OY, Egypt [ 50 ] Case report 1 Patient outcome, PCS in MT of AIS patients The NIHSS score decreased to 2 after reperfusion (from 14 before MT). The importance of PCS implementation and the use of PPE during MT.…”
Section: Main Text (Review Of the Literature Results Discussion)mentioning
confidence: 99%
See 2 more Smart Citations
“…Alharthy et al have shown that in life-threatening COVID-19, especially with immune dysregulation features such as antiphospholipid antibodies, therapeutic plasma exchange could be an effective rescue therapy [109]. Similar to stroke alone, treatment for ischemic stroke in COVID-19 patients is individualized and complicated, including thrombolysis [110,111] and thrombectomy [112,113] for acute interventions and antiplatelets and anticoagulants for secondary prevention. It should be noted that many patients with acute ischemic stroke lose the opportunity for acute intervention because of isolation and reluctance to present to the hospital [114,115].…”
Section: Treatment Of Covid-19-related Strokementioning
confidence: 99%